Hubungan Harga Diri Dan Interaksi Sosial Teman Sebaya Dengan Pengambilan Keputusan Karir Pada Remaja - Khalim, Abdul; , Dr. Sri Lestari, M.Si (2016)
There are many Junior High School graduates did not continue their education or they continue their education without knowing or understanding what subject they will be studied. Junior High School Graduates do not have certain reasons on continuing their study. The aim of the study is to find out the correlation of self esteem and peer social interaction with the caree decicion making on teenagers. The subject of the study is the students of Islamic Junior High School (MTs). The sample is 90 students taken from grade VII, VIII, and IX. The data is collected by Career decicion scale, self esteem scale, and social interaction scale. The data is analized using double linear regression. There 3 result of the study: (1) there is a correlation among self esteem and social peer interaction with career decicion making as much as 0.435 or 45.3%. (2) There is a correlation between self esteem and career decicion making. (3) There is a correlation between peer social interaction with career decicion making.